Strategy Based on Game Theory to Reduce Total Latency in the Location of Controllers in a Software Defined Network - Adasme-Soto, P; Valencia-Cordero, C; Caceres-Ramirez, S (Institute of Electrical and Electronics Engineers Inc., 2022)
Software-defined networks are a set of techniques related to the area of computational networks that resolve the separation between the data plane and the control plane, the controller is the brain of the network. This article develops a strategy to solve the Controller Placement Problem (CPP) in a Software Defined Wide Area Network (SDWAN) with low overall latency. The strategy has been implemented in Python. To measure the effectiveness of the strategy, it has been compared with a traditional K-meas code. The result is that the strategy has a similar execution time and a similar overall latency, even low in some cases. Therefore, this strategy is a good alternative to solve the problem. © 2022 IEEE.